STUDI KEBERADAAN Escherichia coli DAN JAMUR PADA MINUMAN SERBUK YANG DIJUAL DI WILAYAH SEKOLAH DASAR KECAMATAN BANYUMANIK KOTA SEMARANG - Luluk Safura Priyandina; Sri Yuliawati; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Children, especially school children, are susceptible to gastrointestinal diseases caused by certain microorganisms, such as diarrhea resulting from drinking powders contaminated with microorganisms. According to the age group, diarrhea sufferers in Semarang City in 2014 are found in ages> 5 years as many as 24,899 cases (IR = 16/1000 population). Which powder beverages are contaminated with E. coli and fungi as the cause of diarrhea? The study sampled the powder drink sold in the Banyumanik District primary school area and interviewed sellers. A total of 15 brands of powdered beverages in the packaging were brought to the laboratory for the study of the presence of E. coli, coliform and fungi. There were found 7 samples of powder drink that contain coliform positive, 5 samples were positively contaminated by E. coli, also found two other gram negative types namely Alkalignes sp and Shigella sp and 2 types of pathogenic fungi namely Aspergillus fumigatus and Cryptococcus. Through interviews with seller, good knowledge only reached 50% of 20 respondents. Still 55% of sellers have less hygienic processing behavior. The hygiene of its own traders is only 35% good. Sellers’ attitude towards good their hygiene is only 60%. Some brands are still stored by the seller even though it has exceeded the expiration limit and has a broken package such as leaking and powder felt clot. It is expected that the seller does not reuse the products that have passed from the expiry date and the powder beverage production factory to make product withdrawal from the seller if found there are already expired.